Building Interest in Buying Communities with Product Quality, Price, and Reference Groups - Muhammad Syarif Hidayatullah Elmas; Dedi Joko Hermawan; Sas Mita; Izzety Fatinah; Wanda Amallya Ababiel (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2023)
iPhone can now be said to have a distinctive brand image because it uses a distinctive information system. Marketing activities are closely related to the concept of product quality so that what consumers think and feel about a particular brand can make perceived benefits. This study aims to examine the effect of product quality, price, and reference group on the purchase interest of iPhone smartphones among students at Panca Marga University, Probolinggo. In this study using the causal-comparative method. Respondents in this study were students of Panca Marga University, Probolinggo. The questionnaire was distributed to 104 respondents. Sampling was done by purposive sampling technique. Based on the results of research using SPSS. Through the results of this research, it can be concluded that: Simultaneously Product Quality, Price, and Reference Group have a positive and significant effect on Purchase Interest for iPhone smartphones for Panca Marga Probolinggo University Students, Partially Product Quality, Price and Reference Group has a positive and significant effect on Purchase Interest of iPhone smartphones for Panca Marga Probolinggo University Students, and Product Quality has a dominant effect on Purchase Interest of iPhone smartphones for Panca Marga Probolinggo University Students.